Student academic procrastination in online and offline learning - Muhson, Ali; Mulyani, Endang; Susilowati, Nenden; Alwi, Ahmad Chafid; Prilanita, Yeni Nur (Technium Social Sciences Journal, 2024)
Students after attending offline lectures stated that they understood the lecture material better and it was more fun. The purpose of this study is to determine the academic procrastination of students in both offline and online learning, the level of academic procrastination of students, differences in academic procrastination in learning, factors that influence academic procrastination, and the magnitude of the influence of each factor forming it. The analysis technique used is Confirmatory Factor Analysis (CFA) with the Structural Equation Model (SEM) model. ANOVA analysis was used to determine the difference between online and offline learning on self-perception, self-efficacy, self-resilience, and academic procrastination. The results of this study show that there are differences in self-perception, self-efficacy, self-resilience, and academic procrastination owned by students for online and offline learning. Offline learning is considered better for students as evidenced by the fact that when compared to both learning systems (online and offline), offline learning has higher self-perception, self-efficacy, self-resilience, and academic procrastination than online learning.